Desarrollo e implementación de un plan de mantenimiento planificado para la empresa FP Reflectar Panels & Glass S.A.S. (2016)
To perform planned maintenance plan began with the creation of a format for data collection during the first 3 months. So from the start data for the entire project development they were collected. Parallel to this activity, it began to describe the company in all its functions, operation and machinery, which were to intervene, observing the state of maintenance. An encoding process equipment was established and a system criticality was applied to establish that teams implement the plan. Maintenance formats and a database for all activities and frequencies established for critical equipment were developed, the plan was put into operation, the results were evaluated, management indicators were calculated and made analysis performed parts and supplier evaluation.